Pebble-bed design returns [nuclear reactor]. - Weil, J. (IEEE spectrum)
Chicago's Exelon Corp., the largest operator of nuclear plants in the United States, and three international partners will make a decision that could jump-start a nuclear revival. Led by South Africa's state utility Eskom, of Johannesburg, the four will decide whether to continue investing in the pebble-bed modular reactor technology. The concept originated in West Germany in the 1960s and 1970s, and is now experiencing a startling revival. Specifically, the four companies will decide whether to fund a full-scale prototype pebble-bed reactor in South Africa, at Koeberg, near Cape Town. If the South African pebble-bed project moves ahead, Exelon will seek design certification from the US Nuclear Regulatory Commission (NRC), Rockville, Md., so that the technology could be sold as a standardized, off-the-shelf design, like the three advanced light-water designs already precertified by the NRC. Exelon hopes to submit an application for a pebble-bed modular-reactor license to the commission in late 2002, start construction around mid-2005, and begin operations for the first unit about three years later. The pebble-bed concept uses a helium coolant and a graphite moderator. The fuel-uranium dioxide enriched in 235 U to 8-10%-consists of particles coated with two layers of carbon and one of silicon carbide, embedded in a carbon matrix, which act as the principal barrier against radioactive releases. The paper describes the operating features of this technology, the safety aspects and commercial prospects